Community-Based SENORITA Gymnastics for Improving Menopausal Symptoms and Quality of Life Among Postmenopausal Women: A Quasi-Experimental Study - Ekayani, Ni Putu Karunia; Meliati, Linda; Sukaisi, Sukaisi (Chakra Brahmanda Lentera Institute, 2026)
Background: Community-based, low-cost exercise programs are needed to support menopausal health in primary healthcare and resource-limited settings. SENORITA Gymnastics integrates low-impact aerobic exercise and breathing-focused Tera Gymnastics and may be feasible for delivery through community elderly health posts. This study aimed to evaluate SENORITA Gymnastics for its effects on menopausal symptoms and quality of life among postmenopausal women. Methods: A quasi-experimental non-equivalent pretest-posttest control-group study was conducted among 60 postmenopausal women at Posyandu Lansia in the working area of the Gunungsari Primary Health Care Center, West Lombok, Indonesia. Participants were allocated to the SENORITA Gymnastics group (n = 30) or the routine elderly gymnastics/control group (n = 30). SENORITA Gymnastics was delivered in eight sessions, twice weekly for four weeks. Menopausal symptoms were measured using the Menopause Symptom Questionnaire, and quality of life was measured using the WHOQOL-BREF. Data were analyzed using descriptive statistics, between-group comparisons, and exploratory logistic regression. Results: Menopausal symptom scores decreased descriptively in both groups, from 61.77 ± 16.26 to 53.93 ± 13.31 in the SENORITA Gymnastics group and from 67.03 ± 19.03 to 53.40 ± 13.87 in the control group. The numerically larger symptom reduction occurred in the control group. Post-test menopausal symptom scores differed significantly between groups (p = 0.035), with slightly lower scores in the control group. Quality-of-life scores increased descriptively in both groups, from 84.80 ± 10.23 to 88.70 ± 7.67 in the SENORITA Gymnastics group and from 78.93 ± 12.06 to 86.83 ± 8.43 in the control group. Post-test quality-of-life scores differed significantly between groups (p = 0.025). However, the SENORITA group already had higher baseline quality-of-life scores, and the descriptive improvement was larger in the control group. Age was the dominant factor associated with quality of life in the final logistic regression model (adjusted OR = 0.072; 95% CI: 0.019-0.273; p < 0.001). Conclusion: SENORITA Gymnastics is feasible as a community-based health promotion activity for postmenopausal women. However, this study did not demonstrate the superiority of SENORITA Gymnastics over routine elderly gymnastics for reducing menopausal symptoms or improving quality of life. Future randomized or cluster-randomized studies with baseline-adjusted repeated-measures analysis, standardized control conditions, intervention fidelity assessment, and larger multicenter samples are needed.